The Use of Avian Resources by the Forgotten Slaves of Tromelin Island (Indian Ocean). (19th December 2013) - Laroulandie, V.; Lefèvre, C.; Bejenaru, L.; Serjeantson, D.
ABSTRACT On 31 July 1761, the Utile, a French slave ship from the Compagnie française des Indes, illegally loaded with Malagasy slaves, was shipwrecked on the desert islet of Tromelin. Two months after the disaster, the French crew left the island on a boat constructed from the wreckage and abandoned the slaves. Fifteen years later, Chevalier de Tromelin rescued eight survivors. An archaeological excavation recently conducted by M. Guérout and T. Romon revealed how the forgotten slaves adapted themselves to this hostile environment. The Malagasy survived using natural resources of the islet and material from the Utile. This paper, based on the archaeozoological analysis of almost 18 000 bird bones, focuses on their use of avian resources. The Malagasy survivors captured numerous individuals from a breeding colony of sooty tern Onychoprion fuscatus, as indicated by the presence of medullary bone and immature birds. Cut marks and localised burning at the bone extremities testify to the cooking method used. Under‐representation of the bones from the distal extremity of the wing, together with the rare written archives collected after the rescue, give evidence of the utilisation of feathers as raw material. An estimate of the total number of terns and eggs that were collected, compared with historical and modern ornithological observations, allows us to discuss the consequences of human predation on the disappearance of the sooty tern colony from Tromelin Island. Copyright © 2013 John Wiley & Sons, Ltd.